Perceptions of climate variability and change in relation to observed data among two east coast communities in Zanzibar, East Africa. (20th October 2020) - Makame, Makame Omar; Shackleton, Sheona
ABSTRACT: This paper seeks to understand the perceptions of local communities to climate variability and change in relation to observed climatic data. A perception survey, historical timeline and analysis of sea level and meteorological data from the study area were used to achieve this objective. As perceptions regarding different types of climate stimuli are likely to trigger response actions, this study highlights the importance of integrating local perceptions into planning for adaptation. The study suggests that climate change is happening in Zanzibar and is set to intensify as it is directly linked to regional and global events such as ENSO. The perceptions of local communities regarding variability in rainfall, temperature and sea level are highly influenced by the relationship between these elements and their livelihood activities, namely fishing, farming and seaweed farming; their direct experience of shifts in weather patterns; and their recall of past climate. While variability and changes were recognized, the majority of respondents linked this to God's doing, and most had little exposure to the phenomenon of global climate change. Furthermore, while local people's perceptions of rainfall and temperature changes showed some relationship with observed data, their perceptions on sea level rise did not.